Novel modifications to carbon-based electrodes to improve the electrochemical detection of dopamine - Jiang, L; Nelson, G; Doff, J; Foord, J (American Chemical Society, 2016)
In this work, we describe three simple modifications to carbon electrodes which were found to improve the detection of an exemplar neurotransmitter (dopamine) in the presence of physiological interferents (ascorbic acid and/or uric acid). First, the electro-oxidation of ascorbic acid, as a pretreatment, at boron-doped diamond electrode (BDE) interfaces is studied. This treatment did suppress the detection of ascorbic acid oxidation signal, but only in a manner suitable for single-use detection of high concentrations of dopamine (i.e. > 1 µM). Second, the hydrogenation of BDE by electrochemical cathodic treatment and plasma hydrogenation was investigated. Large cathodic, applied potentials (i.e. > −5 V) and hydrogen plasma pre-treatment of BDE lead to the partial and complete oxidization of ascorbic acid before dopamine, respectively. The consequence at hydrogen-plasma treated BDE is the complete electrochemical separation of these two species without any typical catalytic reactions between the analytes. Third, the modification of glassy carbon electrodes with carbon black nanoparticles is explored. This modification enables the simultaneous detection of ascorbic acid, dopamine and uric acid, significantly enhancing the sensitivity of dopamine. Dopamine was best detected using the unconventional route of detecting 5,6-dihydroxyindole, which is made possible by use of carbon-black nanoparticles. The potential of all three studied modifications to be of electro-analytical use is highlighted throughout this work.